A.D.A.M. student atlas of anatomy - Olson, Todd R.; Pawlina, Wojciech (Baltimore : Williams & Wilkins, 1996)
Contains illustrative art, cadaveric photographs, radiographs, and tables designed to help expand a student's appreciation for and understanding of the essentials of human anatomy
Includes index
Keywords: Human anatomy -- Vaccines